دراسة الكفاءة الاقتصادية لإنتاج الفطر المحاري في محافظة اللاذقية - صقر, ابراهيم; جحجاح, محسن; فاضل, نور (Latakia University Journal -Biological Sciences Series, 2018)
The oyster mushroom has special importance for its rich protein, its delicious taste, which make it desirable by consumers, in addition to its short life cycle, and the possibility of growing throughout the year; since Oyster mushroom production is accomplished in simple environmental circumstances with low cost of inputs compared to other crops; in addition to its good yield; we focus on the economic importance of planting oyster mushroom by analyzing its production cost, and indexes of economic efficiency using data collected from site of research Stmarkho Farm. This research has been pursued to achieve the following purposes: 1. Studying the reality of planting mushroom in Lattakia governorate 2. Studying the economic efficiency of oyster mushroom production in Lattakia governorate, and giving some suggestions that help to push forward the process of developing this agriculture. As a result of the study, the following results were obtained. · Net profit achieved yearly reached to 7828.77 Syrian pounds from producing 1 liter of oyster mushroom · Profitability ratio in relation to invested capital amounted to 23.03%, compared to production costs 69.3% · The time period for the restoration of capital for the production of oyster mushroom was 3.06 years. تعود الأهمية الخاصة للفطر المحاري لغناه بالبروتين، وطعمه اللذيذ، مما يجعله مرغوباً من قبل المستهلكين، بالإضافة إلى دورة حياته القصيرة، وإمكانية نموه على مدار السنة. وبما أنّ إنتاج الفطر المحاري يتم في ظروف بيئية بسيطة، وبمدخلات قليلة التكلفة مقارنة بباقي المحاصيل الأخرى، بالإضافة إلى أنّه جيد المردود، فقد تمّ التركيز على الأهمية الاقتصادية لزراعة الفطر المحاري من خلال التكاليف الانتاجية، ومؤشرات الكفاءة الاقتصادية، بالاستناد إلى بيانات ومعطيات تمّ جمعها من موقع البحث (مزرعة ستمرخو). وقد تمّ السعي في هذا البحث لتحقيق الأهداف الآتية: دراسة واقع زراعة الفطر في محافظة اللاذقية. دراسة الكفاءة الاقتصادية لإنتاج الفطر المحاري في محافظة اللاذقية، وتقديم بعض المقترحات التي تساعد على دفع عملية تطور هذه الزراعة. وقد تمّ التوصل في هذا البحث إلى النتائج الآتية: بلغ صافي الربح السنوي المحقق من إنتاج 1 ليتر فطر محاري نحو 7828.77ل.س · بلغ معامل الربحية بالقياس إلى رأس المال المستثمر %، وبالقياس إلى التكاليف الإنتاجية %. بلغ مؤشر زمن استعادة رأس المال لإنتاج الفطر المحاري3.06 سنة.